2012
DOI: 10.1161/hypertensionaha.112.193565
|View full text |Cite
|
Sign up to set email alerts
|

Hemoglobin Level Is Positively Associated With Blood Pressure in a Large Cohort of Healthy Individuals

Abstract: Abstract-It has been hypothesized that an increased hemoglobin level elevates blood pressure. The present study investigated the association between hemoglobin level and systolic blood pressure and diastolic blood pressure in healthy persons. The study population was composed of 101 377 whole blood and plasma donors, who made 691 107 visits to the blood bank. At each visit, hemoglobin level and blood pressure were measured as part of the standard procedure before a blood donation. We used repeated measurement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
105
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 128 publications
(119 citation statements)
references
References 23 publications
11
105
2
1
Order By: Relevance
“…Moreover, this association was observed only among the participants with a BMI of <25 kg/m 2 . A Dutch study of 691,107 voluntary blood donors reported that the hemoglobin levels are positively associated with both systolic and diastolic blood pressure (7). A Germany study of 1,013 unselected persons showed a significant correlation between the hemoglobin levels and blood pressure and a statistically significant correlation between the mean (as well as systolic and diastolic) arterial blood pressure and hemoglobin concentration (r=0.29; p< 0.0001) (4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, this association was observed only among the participants with a BMI of <25 kg/m 2 . A Dutch study of 691,107 voluntary blood donors reported that the hemoglobin levels are positively associated with both systolic and diastolic blood pressure (7). A Germany study of 1,013 unselected persons showed a significant correlation between the hemoglobin levels and blood pressure and a statistically significant correlation between the mean (as well as systolic and diastolic) arterial blood pressure and hemoglobin concentration (r=0.29; p< 0.0001) (4).…”
Section: Discussionmentioning
confidence: 99%
“…Another study reported that treatment with erythropoiesisstimulating proteins used to treat anemia in hemodialysis patients is related to elevated blood pressure (6). Moreover, a Dutch study with a large number of healthy volunteer blood donors reported a positive association between the hemoglobin levels and blood pressure (7).…”
Section: Introductionmentioning
confidence: 99%
“…We used the same dataset as the one used in a previous study on the association between blood pressure and Hb. 25 In this dataset, visits with missing blood pressure measurements (n ¼ 8981) or Hb measurements (n ¼ 1193) have been excluded. 25 In the end, the study data file consisted of 691,107 measurements obtained from 101,377 whole blood donors and plasma donors.…”
Section: Study Populationmentioning
confidence: 99%
“…25 In this dataset, visits with missing blood pressure measurements (n ¼ 8981) or Hb measurements (n ¼ 1193) have been excluded. 25 In the end, the study data file consisted of 691,107 measurements obtained from 101,377 whole blood donors and plasma donors. The number of measurements per donor ranged from one to 69 in 3 years.…”
Section: Study Populationmentioning
confidence: 99%
“…There are few reports for the normal population. Atsma et al [8] have shown that Hb level is positively associated with blood pressure in a large Dutch cohort of healthy individuals who were voluntary blood donors. The main objective of this study was to investigate the association between Hb levels and SBP and DBP in a Chinese community-dwelling cohort.…”
Section: Introductionmentioning
confidence: 99%